Construction Mechanical Response Analysis of City Railway Machinary Method Link Passage under Eccentric Opening Conditions - LI Yitao; SUN Shuangchi; YU Jing; ZHOU Meng; WANG Wenzhong (Chengshi guidao jiaotong yanjiu)
[Objective] The machinery construction method for link passages has been widely applied in 6-meter-class diameter shield tunnels, typically used in metro projects. However, there are few engineering practice cases and the limited research regarding its application in city railway tunnels, where 9-meter-class large-diameter shields are used. [Method] Focusing on a city railway project with 9-meter-class diameter shield tunnel, a three-dimensional load structure model of main tunnel and link passage is established. Under varying conditions of burial depth, soil parameter, and shield machine thrust, the impact of link passage construction on the main tunnel structure is analyzed from three aspects: deformation, axial force, and bending moment of special segments under different operating conditions. [Result & Conclusion] The additional deformation caused by the construction of link passage is influenced by both the burial depth and the thrust of the shield machine. When the burial depth is large, the link passage construction will increase the convergence deformation of the main tunnel; when the burial depth is small, it reduces the convergence deformation. An increase in shield machine thrust further reduces the convergence deformation of the main tunnel. Changes in the main tunnel internal forces are mainly concentrated in the steel segment sections of the three-ring special segments, where the axial force and bending moment at the arch waist of semi-open segment significantly increase, with the maximum occurring under operational conditions, which requires special attention during design. In contrast, internal force changes in the concrete segments are relatively minor.